2012
DOI: 10.14742/ajet.889
|View full text |Cite
|
Sign up to set email alerts
|

Using a wiki-based collaborative process writing pedagogy to facilitate collaborative writing among Chinese primary school students

Abstract: <span>This case study explored collaborative writing in Chinese among 59 primary four Chinese students using a </span><em>Wiki-based Collaborative Process Writing Pedagogy</em><span> (WCPWP) in Shenzhen, China. It aimed mainly to design and orchestrate a WCPWP in order to facilitate students' Chinese writing. It investigated students' collaborative writing process and their performance on a wiki, and explored the perceptions and attitudes of the teacher and her students towards WC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(27 citation statements)
references
References 18 publications
2
23
0
2
Order By: Relevance
“…Ma and Yuen (2008) who studied on student journalists learning news writing report that wikis effectively facilitate learners' writing processes; particularly their revision behaviour and this eventually improve their writing performance. In addition, the study by Li et al (2012) reveals that with wikis, students are more motivated to look for additional information on the web as they are already online and this encourages them to learn new vocabulary and language forms which contribute to improved writing.…”
Section: Perceived Usefulnessmentioning
confidence: 99%
“…Ma and Yuen (2008) who studied on student journalists learning news writing report that wikis effectively facilitate learners' writing processes; particularly their revision behaviour and this eventually improve their writing performance. In addition, the study by Li et al (2012) reveals that with wikis, students are more motivated to look for additional information on the web as they are already online and this encourages them to learn new vocabulary and language forms which contribute to improved writing.…”
Section: Perceived Usefulnessmentioning
confidence: 99%
“…More exciting and invigorating, Mixed Between-Within-Subjects ANOVA (two-way RANOVA) indicated that DWCPWP had a significantly positive effect on the writing attitudes of students [7]. However, the results showed that DWCPWP had a positive but insignificant effect on students' writing ability.…”
Section: Introductionmentioning
confidence: 92%
“…However, the results indicated that the WCPWP was far more from perfect and there was much room for improvement [6]. Li, Chu and Ki improved the WCPWP [7], which can be named as Developing Wiki-based Collaborative Process Writing Pedagogy (DWCPWP).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, social network analysis method that investigating relationships among group members (Aviv et al 2003;De Laat et al 2007) content analysis method that analyzing the knowledge construction (Weinberger and Fischer 2006) or depth of understanding (Zhang et al 2009), conversation analysis that identifying action sequences or turn-taking (Zemel et al 2005), interviews or questionnaires for evaluating the perceptions of students during collaborative learning (Jarmon et al 2009;Li et al 2012;Prokofieva 2013). However, the assessment of collaborative learning processes as well as learning outcomes from the perspective of knowledge convergence remains lacking.…”
Section: Related Workmentioning
confidence: 99%